Analisis Kelayakan Usaha Rumah Potong Hewan Ditinjau Dari Aspek Teknis Dan Sumber Daya Manusia - Helfi Fitron Almakhali; Mochamad Reza Adiyanto; Eni Sri Rahayuningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The research aims to determine the feasibility of slaughterhouse businesses in East Java, in terms of technical and human resource aspects. This research uses descriptive qualitative methods. Sampling was carried out using purposive sampling technique and data collection used primary data. The data analysis tool used is cross tabulation. The objects of this research are the slaughterhouse in Krian, Sidoarjo and the poultry slaughterhouse in Jombang (CV. RAFIKA FOODS INDONESIA). The results of the analysis from this research on the technical aspects of ruminant slaughterhouses are 86% and poultry slaughterhouses are 84% in compliance with Minister of Agriculture Regulation number 13 of 2010. In the human resources aspect ruminant slaughterhouses and poultry slaughterhouses have complied with Minister of Agriculture Regulation No. 13 2010. From these results, it is stated that ruminant slaughterhouses and poultry slaughterhouses are feasible to run. Keywords: Technical, Human Resource Aspect. Slaughterhouse